Inorganic polyphosphate enhances radio-sensitivity in a human non–small cell lung cancer cell line, H1299 - Kaori Tsutsumi; Yusuke Matsuya; Tomoki Sugahara; Manami Tamura; Satoshi Sawada; Sagiri Fukura; Hisashi Nakano; Hiroyuki Date (Tumor Biology)
Inorganic polyphosphate is a linear polymer containing tens to hundreds of orthophosphate residues linked by high-energy phosphoanhydride bonds. Polyphosphate has been recognized as a potent anti-metastasis reagent. However, the molecular mechanism underlying polyphosphate action on cancer cells is poorly understood. In this study, we investigated the involvement of polyphosphate in radio-sensitivity using a human non–small cell lung cancer cell line, H1299. We found that polyphosphate treatment decreases cellular adenosine triphosphate levels, suggesting a disruption of energy metabolism. We also found that the induction of DNA double-strand breaks was enhanced in polyphosphate-treated cells after X-ray irradiation and colony formation assay revealed that cell survival decreased compared with that of the control groups. These findings suggest that polyphosphate is a promising radio-sensitizer for cancer cells. Therefore, we hypothesized that polyphosphate treatment disrupts adenosine triphosphate–mediated energy transfer for cellular survival and DNA repair, thereby reducing the cellular capability to resist X-ray irradiation.